Various Properties of Convoluted Special Polynomials Associated with Bell Polynomials and Their Algebraic Characteristics (European Journal of Pure and Applied Mathematics, 2026)
This paper uses generating functions to present Bell polynomials of two variables associated with Appell sequences. We investigate their diverse properties, including explicit representations, summation formulae, recurrence relations, and addition formulas. Furthermore, we introduce the second kind's Bell-Appell-based Stirling polynomials in two variables and outline their associated findings. This research enhances comprehension regarding the attributes and utility of Bell-Appell and Bell-Appell based Stirling polynomials in mathematical analysis. Further, determinant representation, operational identity and other characteristics are derived.
Keywords: Hybrid special polynomials; Monomiality principle; Determinant representation; explicit forms; Summation Formulae; Operational rule